On possibility of creating hydrodynamic noise distributed silencer in single-flow rubber cord pipe - Yu. A. Burian; A. V. Zubarev; S. N. Polyakov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The paper considers the principal possibility to increase the efficiency of rubber-cord single-flow pipe branches with the help of an organization in the framework of a single construction with flexible insertion of a waveguide silencer absorber of hydrodynamic noise. It is shown that the filling of the space between the pipe branch body and the inner rubber tube with flexible walls with porous rubber with metallic inclusions forms a waveguide sound silencer. In the model example, the frequency range boundaries of the sound wave locking in the device under consideration are determined